(untitled) (Raparin Journal of Humanities (RJH), 2025)
This paper investigates the types of figurative and phonological features used by Dorothy Parker in her poem “A Dream Lies Dead.” Based on Geophry Leech and Mick Short’s (2007) framework of literary analysis, the poem employs various figurative and phonological schemes, including imagery, metaphor, personification, hyperbole, and anaphora, as well as rhyme, repetition, assonance, and consonance. The paper addresses three main questions related to the types of grammatical and lexical schemes used in the poem, the most frequent one(s) applied, and the poetess’s purpose behind using them. To accomplish the study, the heuristic checklist of linguistic and stylistic categories, presented by Leech and Short (2007), was applied. The checklist included basic levels of analysis which included lexical categories, grammatical categories, figures of speech, context, cohesion, and semantic features. The semantic features in the framework are separated, as they could be accessed through other categories and conveyed through basic language structures. Results of the analysis showed frequent usage of various figurative and phonological devices reflecting the poetess’s feelings and spiritual state that prevail through the poem. Among several linguistic features, personification, imagery and metaphor were mostly used to express all types of meanings conveyed in the poem and, at the same time, enhance the humanitarian phase with all the emotions and struggles people experience.